Ideas of Renunciation Found in Buddhist Manual and A Sufi Text - Cousens, Dr. Diana (South Asian Journal of Religion and Philosophy (SAJRP), 2024)
Significant parallels in approaches to spiritual life can be found through a close reading of the 11th century CE Persian Sufi text, the Kashf al-Mahjub by the Ghazni-born al-Hujwiri, and the third century CE Mula Sarvastivadin Rules for a Novice Monk, based on the Buddhist code of monastic discipline, the Vinaya. While the injunctions and rules are presented very differently both emphasise a spirit of renunciation. Buddhist monastics follow a very clear set of rules which are documented and are binding, whereas Al-Hujwiri describes characteristics of a spiritual path using an oral tradition and anecdotes. However, in both traditions we find small communities of followers living with teachers, observing codes of discipline, wearing an identifiable robe, travelling with limited possessions and undertaking different kinds of austerities such as fasting. While there are significant differences in theology between Sufism and Buddhism, there is common ground in their attitude to renunciation.